Nurses’ experiences of using falls alarms in subacute care: A qualitative study - Julie Considine; Debra Berry; Maureen Mullen; Edmore Chisango; Melinda Webb-St Mart; Peter Michell; Peteris Darzins; Leanne Boyd (PLoS ONE, 2023)
Bed and chair alarms have been included in many multifaceted falls prevention interventions. None of the randomised trials of falls alarms as sole interventions have showed significant effect on falls or falls with injury. Further, use of bed and chair alarms did not change patients’ fear of falling, length of hospital stay, functional status, discharge destination or health related quality of life. The aim of this study was to explore nurses’ experiences of using bed and chair alarms. A qualitative descriptive study using semi-structured interviews with a purposive sample of 12 nurses was conducted on a 32-bed Geriatric Evaluation and Management ward in Melbourne, Australia. Participants were interviewed between 27 January and 12 March 2021.Transcribed audio-recordings of interviews were analysed using inductive thematic analysis. NVIVO 12.6 was used to manage the study data. Three major themes and four subthemes were constructed from the data: i) negative impacts of falls alarms (subthemes: noisy technology, imperfect technology), ii) juggling the safety-risk conflict, and iii) negotiating falls alarm use (subthemes: nurse decision making and falls alarm overuse). Nurses’ experience of using falls alarms was predominantly negative and there was tension between falls alarms having limited impact on patient safety and risks associated with their use. Nurses described a need to support nurse decision making related to falls alarms use in practice and policy, and a desire to be empowered to manage falls risk in other ways.